Optical and Wireless Technologies Proceedings of OWT 2019 - Janyani, Vijay; Singh, Ghanshyam; Tiwari, Manish; Ismail, Tawfik; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This volume presents selected papers from the 3rd International Conference on Optical and Wireless Technologies, conducted from 16th to 17th March, 2019. It focuses on extending the limits of currently used systems encompassing optical and wireless domains, and explores the latest developments in applications like photonics, high speed communication systems and networks, visible light communication, nano-photonics, wireless, and MIMO systems. The proceedings contain high quality scholarly articles, giving insight into the analytical, experimental, and developmental aspects of systems, techniques, and devices in these spheres. This volume will prove useful to researchers and professionals alike.
Optical Materials -- Optical Signal Processing -- Optical Networking -- Photonic Communications Systems and Networks -- All-Optical Communication Systems -- Energy-Efficient & Spectral-Efficient Optical Communication Systems -- Microwave Photonics -- Optical Fibers and Devices for Optical Communications -- Optical Amplifiers -- Nonlinear Optics -- Nanophotonics -- Software-defined Radio and Cognitive Radio -- Signal Processing for Wireless Communications -- Antenna Systems -- Plasmonics and Nanoantennas -- Spectrum Management and Regulatory Issues -- Intelligent Transportation System & Vehicular Communications -- Wireless Sensor Networks -- Machine-to-machine Communications -- MAC Layer and Routing Protocols -- Cellular-Wi-Fi Integration and interworking -- Integration of Optical and Wireless Networking -- Lasers and Photonic Components -- High Speed Optical LANs and Gigabit Ethernet -- Optical Amplification and Sensing -- Optical Networks Performance Modeling -- Energy Efficiency in Optical Networks -- Reliability and Protection in Optical Networks -- New Architectures for Optical Routers and Switches -- and New Optical Fiber Technologies.
Keywords: Telecommunication; Wireless communication systems; Mobile communication systems; Lasers; 9; Microwaves, RF Engineering and Optical Communications; Wireless and Mobile Communication; Laser; Computer Communication Networks